Peran Guru dalam Menerapkan Model Kooperatif Learning Tipe NHT (Numbered Head Together) di Sekolah Dasar - Firda Widya Sari; Irani Putri Damayanti; Wulan Sutriyani (Jurnal Humaniora dan Ilmu Pendidikan, 2022)
Learning activities can be said to be successful when learners are active and have a passion in the learning process, so the learning result can increase. One way to overcome that is by applying the learning model. There are many learning models that can be applied in the learning process. one of those learning models is the NHT. The counter-head together (NHT) model is a cooperative model that divides learners into small groups ranging from four to four to one hegeneous, given in head or in the hands of a number, and it trains learners to work with each other to think of the answers that teachers ask each other. Purpose: The purpose of the study is to identify the role of the NHT (free-heads together) learning model to improve learners' learning subjects and to encourage educators or potential educators to adopt the cooperative course of counter-heads together (NHT). Methodology: The study is a qualitative study of library study. Results: Based on data analysis from previous studies and various references, it can be concluded that the NHT cooperative learning model can increase the learning result of the lesson.